Melanin: a unifying theory of disease as exemplified by Parkinson’s, Alzheimer’s, and Lewy body dementia - Berg, Stacie Z.; Berg, Jonathan (Frontiers in Immunology, 2023)
Melanin, a ubiquitous dark pigment, plays important roles in the immune system, including scavenging reactive oxygen species formed in response to ultraviolet radiation absorption, absorbing metals, thermal regulation, drug uptake, innate immune system functions, redox, and energy transduction. Many tissue types, including brain, heart, arteries, ovaries, and others, contain melanin. Almost all cells contain precursors to melanin. A growing number of diseases that have a loss of melanin and/or neuromelanin are increasingly thought to have infectious etiologies, for example, Alzheimer’s disease (AD), Parkinson’s disease (PD), Lewy Body Dementia (LBD), and vitiligo. AD, PD, LBD, and vitiligo have been linked with herpesvirus, which enters melanosomes and causes apoptosis, and with gut dysbiosis and inflammation. Herpesvirus is also linked with gut dysbiosis and inflammation. We theorize that under normal healthy states, melanin retains some of the energy it absorbs from electromagnetic radiation, which is then used to fuel cells, and energy from ATP is used to compliment that energy supply. We further theorize that loss of melanin reduces the energy supply of cells, which in the case of AD, PD, and LBD results in an inability to sustain immune system defenses and remove the plaques, which appear to be part of the immune system's attempt to eradicate the pathogens seen in these neurodegenerative diseases. In addition, in an attempt to explain why removing these plaques does not result in improvements in cognition and mood and why cognitions and moods in these individuals have ebbs and flows, we postulate that it is not the plaques that cause the cognitive symptoms but, rather, inflammation in the brain resulting from the immune system response to pathogens. Our theory that energy retained in melanin fuels cells in an inverse relationship with ATP is supported by studies showing alterations in ATP production in relationship to melanin levels in melanomas, vitiligo, and healthy cells. Therefore, alteration of melanin levels may be at the core of many diseases. We propose regulating melanin levels may offer new avenues for treatment development.